PERLINDUNGAN HUKUM BАGI KORBАN TINDАK PIDАNА PENIPUАN JUAL BELI ONLINE DI INDONESIA - Dea Larissa Dea Larissa Deah (Riau Law Journal, 2020)
The development of technology and information led to new innovations related to the model in the trading system, namely Online Buying and Selling. The world economy and current international trade competition can have negative implications for consumer protection in online trading in Indonesia. The research method uses a descriptive qualitative approach that is by understanding various concepts found in the research process, research techniques using content analysis and library research. This research aims to find out how legal protection for victims of online buying and selling scams in Indonesia.